Polyethylene Insert Exchange Is Crucial in Debridement for Acute Periprosthetic Infections following Total Knee Arthroplasty - Zhang, Chaofan; Yan, Chun Hoi; Chan, Ping Keung; Ng, Fu Yuen; Chiu, Kwong Yuen (The Journal of Knee Surgery, 2017)
This study aims to report our experience of managing acute periprosthetic joint infection (PJI) following total knee arthroplasty (TKA) with surgical debridement and prostheses retention. A review of patients in our prospective joint replacement register from 1998 to 2013 was performed. In this study, 34 patients with 35 TKAs were included; 25 were infections after primary TKA and 10 were after revision TKA. For primary TKA infections, after a mean follow-up of 53.8 ± 42.6 months, 11 were successfully treated, while 14 failed, including 10 required reoperations and 4 needed lifelong antibiotic suppression. The success rate of debridement was 44.0%. Statistical analyses showed no significant differences between the two groups on patients' age, time lag between symptoms onset and debridement, preoperative C-reactive protein, erythrocyte sedimentation rate, white blood cell count, hemoglobin, albumin, glucose, or synovial fluid total cell count. Patients' primary diagnoses or staphylococcal infections had no significant impact on the surgical outcomes either. Debridement with polyethylene insert exchange had significantly higher success rate than debridement alone, with all 13 cases without exchange failed. All 10 cases with infections after revision TKA had failed. We concluded that debridement with prostheses retention has a low success rate for acute PJI following primary TKA. The polyethylene insert should be exchanged during surgery. For acute infections after revision TKA, total revision should be contemplated.
Keywords: total knee arthroplasty; acute periprosthetic infection; debridement; prostheses retention; polyethylene insert exchange